2008
DOI: 10.1093/brain/awn013
|View full text |Cite
|
Sign up to set email alerts
|

Music listening enhances cognitive recovery and mood after middle cerebral artery stroke

Abstract: We know from animal studies that a stimulating and enriched environment can enhance recovery after stroke, but little is known about the effects of an enriched sound environment on recovery from neural damage in humans. In humans, music listening activates a wide-spread bilateral network of brain regions related to attention, semantic processing, memory, motor functions, and emotional processing. Music exposure also enhances emotional and cognitive functioning in healthy subjects and in various clinical patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
311
0
25

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 646 publications
(356 citation statements)
references
References 77 publications
20
311
0
25
Order By: Relevance
“…It was experienced while listening to music and singing [92] but also following choir participation, which may be generated by hormonal and related immune changes [18,48]. This is consistent with literature on music therapy for stroke [35,37], along with a similar study involving choral singing solely for people with aphasia [34]. However, only one study to date has indicated that music therapy showed improved mood in PD [93].…”
Section: Therapeutic Benefits Of Cstsupporting
confidence: 75%
See 1 more Smart Citation
“…It was experienced while listening to music and singing [92] but also following choir participation, which may be generated by hormonal and related immune changes [18,48]. This is consistent with literature on music therapy for stroke [35,37], along with a similar study involving choral singing solely for people with aphasia [34]. However, only one study to date has indicated that music therapy showed improved mood in PD [93].…”
Section: Therapeutic Benefits Of Cstsupporting
confidence: 75%
“…Singing employs greater neural circuitry [30,31], which may be preserved following a stroke [32]; indeed people with aphasia can often sing despite an inability to speak [33]. Small-scale singing studies with stroke survivors show improved mood [34,35], QOL [36], neuroplasticity [37], and word production [36,38]. Choral singing may also prevent voice decline [39] and improve QOL in PD [18].…”
Section: Choral Singing Therapy As a New Approach To Enhance Living Wmentioning
confidence: 99%
“…Research has centred around two main threads: (1) the impact of listening to music and (2) the impact of making music. Studies focused on listening to music have evidenced a positive influence on stress reduction (Pelletier, 2004), emotional regulation and personal mood management (DeNora, 2000; Hays & Minichiello, 2005; Sloboda, 1999), pleasure and the arousal of positive emotions (Gabrielsson, 2011; Laukka, 2007; Salimpoor, Benovoy, Larcher, Dagher, & Zatorre, 2011), social bonding (Nilsson, 2008), and enhancement of cognitive functioning after neurological impairment (Särkämö, Tervaniemi, & Laitinen, 2008). Additionally, listening to music has been linked to an attribution of meaning in daily life for vulnerable populations such as older adults (Hays & Minichiello, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] In essence, the more time one devotes to learning a certain motor skill the better the performance. The potential role of music in neurological rehabilitation was assessed by Sarkamoet al 31 Study results showed that recovery in the domains of verbal memory and focused attention improved significantly more in the music group than in the language and control groups According to Ericsson et al studies examining a doseresponse association in obtaining skills have provided insight about the most significant factor that differentiates the superiority of certain domain-related actions as carried out by experts (or professionals) while at the same time those achieved by less talented people is actually the duration of time that is dedicated to practicing the craft to acquire the particular skill. 28 Recognizing the role of rehabilitation can be mostly observed as a development in which the patients are educated to achieve compound motor tasks such as dressing, walking and washing.…”
Section: Discussionmentioning
confidence: 99%